1038. IRIS JUNONIA: Iridaceae. (26th August 2022) - Rix, Martyn; Güner, Adil; Mathew, Brian; Barlow, Gillian; Brown, Andrew
Summary: Iris junonia Schott & Kotschy ex Schott, a wonderfully scented tall bearded iris, is illustrated; its ecology is described and its relationship to other bearded irises is discussed.